Ab initio study: the potential energy curves and ro-vibrational spectrum of low-lying excited states of HCl+ cation. (1st October 2016) - Liu, Yajun; Cheng, Xinlu; Cheng, Huajun; Cheng, Junxia; Song, Xiaoshu
ABSTRACT: The potential energy curves (PECs) of 11 electronic states of HCl + cation are obtained by using the high-level relativistic multi-reference configuration interaction plus Davidson correction (MRCI + Q) method. The spin-orbit coupling effect is also taken into account in electronic structure calculations. The PECs of X 2 Π and A 2 Σ + states accord well with corresponding Rydberg--Klein–Rees PECs. The spectroscopic constants for the bound states of HCl + agree well with available theoretical and experimental data. The dipole moments (DMs) and transition dipole moment of the X 2 Π→A 2 Σ + are also in agreement with previous results. According to the PEC and DM, we calculated Einstein A -coefficients and ro-vibrational line intensities of 1–0, 2–0, 2–1, 3–0, 3–1, 4–0 and 4–1 bands for X 2 Π1/2 state. Abstract :